How Does Innovation Unfold? The Relationship between Self-regulatory Processes and Creative Performance - BLEDOW, Ronald Joachim (Institutional Knowledge at Singapore Management University, 2013)
Creative performance is critical for the success of individuals and organizations in dynamic environments. In order to have a positive impact, attempts to increase creative performance need to be based on a well-developed understanding of the psychological processes that underlie creative performance. The present study aims to contribute to this understanding theoretically and empirically. It examines relations between self-regulatory processes and creative performance on real word projects. Based on Personality Systems Interaction Theory processes of self-regulation are specified that uniquely contribute to creative performance: Self-determination, planning, an iterative procedure and positive fantasies. The degree of exploration and exploitation that is demanded in a job is examined as a moderating boundary condition of self-regulatory processes. Hypotheses were tested using the event-reconstruction method with multi-source data of employees and managers on 202 projects in a variety of creative professions and industries. Results of multilevel modeling confirmed the unique positive relations between self-determination, planning, an iterative procedure and creative performance. Planning was most strongly related if a person’s job demanded a balanced level of exploitation and exploration. Positive fantasies were only related to creative performance if jobs demanded high levels of exploration. The strengths and weaknesses of the study’s method are discussed and the practical implications for facilitating creative performance are discussed.